2014
DOI: 10.9734/arrb/2014/10073
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Patterning: An Important Taxonomic Tool for Systematical Studies of Tree Species of Angiosperm

Abstract: Taxonomic information provides the base line for most of the studies in biological sciences. Most of taxonomic information based on phenotypic characteristics of plants. As phenotypic markers are under the influence of environment, therefore it may leads toward the taxonomic confusion. Therefore, present study was carried out to determine the effect of environment on types of stomata, number, size, and stomata patterning which is very useful feature in taxonomy. In the present study thirty arboreal species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(27 reference statements)
0
8
0
3
Order By: Relevance
“…30 Brachyparacytic stomata were found on the adaxial surface and were surrounded by irregular wavy cells. 51 Microscopic examination of leaves revealed the polygonal shape of upper and lower epidermal cells. The vascular bundle was encircled in a sclerenchymatous ring in the midrib region, while multi-layered spongy tissue and single-layered palisade tissue were present in the mesophyll region.…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…30 Brachyparacytic stomata were found on the adaxial surface and were surrounded by irregular wavy cells. 51 Microscopic examination of leaves revealed the polygonal shape of upper and lower epidermal cells. The vascular bundle was encircled in a sclerenchymatous ring in the midrib region, while multi-layered spongy tissue and single-layered palisade tissue were present in the mesophyll region.…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…The physiological function of the stomata was related to the number, density, distribution pattern, and morphological properties (Harrison et al, 2020;Khan et al, 2014).The high density of stomata supported leaves with a broad surface in order to get sufficient CO2 intake for the photosynthesis process and to help the leaves to carry out the transpiration process quickly (Raven et al, 2011). The aim was to reduce the temperature in the mesophyll tissue (cooling down process).…”
Section: Total Of Individuals 138mentioning
confidence: 99%
“…The function of the stomata is directly related to their distribution pattern. All different divisions of plants have differences of stomata distribution pattern in which the distribution pattern is not only under control genetics, but also the environmental factors, such as light intensity, humidity, temperature, atmospheric carbon dioxide and nutrient availability (Croxdale, 2000;Khan et al, 2014;Kushwaha et al, 2018;Pourkhabbaz et al, 2010). Therefore, it is important for us to investigate the stomata properties related to the protective function of shade tree leaves.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the use of leaf margin descriptors are useful in the automated leaf identification process (Cerutti et al, 2014). Khan et al (2014) reported that stomata type was found not plastic to environmental changes (e.g., temperature gradient). This is despite the reports on the plasticity of other stomatal characteristics such as size and density to water and temperature manipulations (Fraser et al, 2008;Bañon et al, 2004).…”
Section: Distinctive Leaf Characters Across Speciesmentioning
confidence: 99%